Analysis of Satisfaction Level with Hajj Registration Services using Fuzzy Service Quality and Importance Performance Analysis - Aditya Rivaldi; Herfina Herfina; Mulyati Mulyati (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2022)
Service is an activity that is interactive between communities that aims to provide satisfaction and comfort. To achieve this goal, it is necessary to improve the quality and quality of services as well as in the Hajj registration service. The purpose of this study was to analyze the level of satisfaction with Hajj Registration Services using the Fuzzy Service Quality (Servqual) and Importance Performance Analysis (IPA) methods. The data collection technique in this study used 100 questionnaires. The statement items used refer to the dimensions of service quality, namely reliability, responsiveness, assurance, empathy and physical evidence and the methods used to analyze are service quality (servqual) and Importance Performance Analysis (IPA). The servqual method will measure the service quality of each dimension so that the gap value is obtained which is the difference between expectations and reality received by the registrant. The servqual method is then integrated with Importance Performance Analysis to classify certain service quality attributes. The results showed that the Hajj registrants were not satisfied with the quality of services provided by the Ministry of Religion in Kabupaten Bogor by showing a negative servqual score. Based on the results of the IPA, there are 9 attributes that are in quadrant B and quadrant C, 3 attributes that are in quadrant D and none of them are in quadrant A. Therefore, improving service quality needs to be carried out by the Ministry of Religion in Kab. Bogor.